The Epistemic Value of Open Science - Chavanayarn, Siraprapa (Open Science Journal, 2018)
Open science refers to all scientific culture that is described by its openness. It may often include features of open access, open data, and open source. Fecher and Friesike (2014) identify five open science schools of thought: the public school, which is about the accessibility of knowledge creation; the democratic school, which is about equality of access to knowledge; the pragmatic school, which is about collaborative research; the infrastructure school, which is about the technological architecture; and the measurement school, which is about alternative impact measurement. This article argues that there are only two open science schools, the public and democratic iterations, that can defend themselves against the serious epistemic objections to open science. In addition, if society supports an “open discussion” policy, societies will gain much more benefit from open science. These two schools, therefore, have more epistemic value than the other schools.